Memahami Kesulitan Implementasi Nilai-nilai Universal Hak-Hak Asasi Manusia Internasional - Agussalim Agussalim (Jurnal Paradigma, 2012)
The developing of the human right norms and values in the international for a not brings the increasing of the human right conditions automatically. There are some obstacles to implement the norms. It is difficult to implement the human right idea universally that could be received by all states. This paper describes the factors that make difficulties on states in the implementing of the human right.